Burkina Faso : Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Press Release on the Executive Board Discussion. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper presents Burkina Faso's third review under the Three-Year Arrangement under the Poverty Reduction and Growth Facility. Favorable weather augurs well for a rebound in agricultural production, but real GDP growth is expected to remain below trend in the near term. A good harvest would contribute to an easing of inflation pressures, supported by lower international oil and food prices. Domestic supply will largely determine developments in 2009. The main risks relate to further deterioration of the external environment, especially indirect effects of the global financial turmoil.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet